Detecting EGFR mutations and ALK/ROS1 rearrangements in non‐small cell lung cancer using malignant pleural effusion samples - Yao, Yi (Thorac Cancer, 2018)
BACKGROUND: The study was conducted to evaluate the feasibility of using malignant pleural effusion (MPE) as a substitute specimen for genetic testing and to determine the significance of genetic profiling of MPE tumor cells to monitor non‐small cell lung cancer (NSCLC) progression and therapeutic response. METHODS: We selected 168 NSCLC patients with MPE. We extracted MPE and enriched tumor cells using a custom‐designed device. EGFR mutations and ALK/ROS1 fusions were then detected by quantitative real‐time PCR, and the results were used to guide targeted therapy. We investigated drug responses through imaging. RESULTS: MPE tumor cells were detected in all patients. EGFR mutations and ALK/ROS1 rearrangements were detected in biopsy samples, treated MPE, and untreated MPE. We found that treated MPE had higher sensitivity and specificity than biopsy or untreated MPE. Among the 26 EGFR inhibitor patients, 13 showed a partial response, 7 had progressive disease, and 6 showed stable disease. Among the 16 patients that received ALK/ROS1 inhibitors, 8 had a partial response, 4 had progressive disease, and 4 showed stable disease. CONCLUSION: Our study provides a new, less invasive, and highly repeatable method of analyzing MPE tumor cells in NSCLC that facilitates precision medicine and genetic testing.